PEMBELAJARAN MAHARAH QIRA’AH DENGAN MODEL DISCOVERY LEARNING: PEMBELAJARAN MAHARAH QIRAAH DENGAN MODEL DISCOVERY LEARNING - sa'diyah, chalimatus; santi supriyani (Arabic Language and Education, 2024)
Abstrac: This research discusses the history and understanding of Discovery Learning, the advantages and disadvantages of Arabic Language Learning Maharah Qira'ahith Discovery Learning model, Implementation of Arabic Language Learning Maharah Qira'ah with Discovery Learning model. This research uses library research method, which is a method of examining and observing data, books, papers, journals and theses related to the discussion. In learning maharah qiro'ah there are many learning models, one of which is Discovery Learning. Discovery learning is a method to develop an active way of learning students by determining themselves, investigating themselves, then the results obtained will be faithful, and long-lasting in memory and will not be easily forgotten by students. One of the goals of this problem is to make learners' memories long-lasting about the knowledge that has been examined and researched. Discovery Learning is a model discovered by several experts, but this learning model was developed by Jerome Bruner in the 1960s. This method emphasizes student activeness in learning and students are required to learn independently of student experience. However, this learning does not always run effectively, because it must adjust the ability of students and see the situation. There are advantages and disadvantages in Discovery Learning, but these weaknesses can be overcome with certain strategies. Abstrak: Penelitian ini membahas tentang sejarah dan pengertian Discovery Learning, kelebihan dan kekurangan Pembelajaran Bahasa Arab Maharah Qira'ah dengan model Discovery Learning, Implementasi Pembelajaran Bahasa Arab Maharah Qira'ah dengan model Discovery Learning. Penelitian ini menggunakan metode penelitian kepustakaan (library research), yaitu suatu metode dengan cara menelaah dan mengamati data-data, buku-buku, makalah, jurnal dan skripsi yang berkaitan dengan pembahasan. Dalam pembelajaran maharah qiro'ah terdapat banyak model pembelajaran, salah satunya adalah Discovery Learning. Discovery learning adalah suatu metode untuk mengembangkan cara belajar siswa aktif dengan cara menentukan sendiri, menyelidiki sendiri, maka hasil yang diperoleh akan setia, dan tahan lama dalam ingatan dan tidak akan mudah dilupakan oleh siswa. Salah satu tujuan dari masalah ini adalah membuat ingatan peserta didik tahan lama tentang pengetahuan yang telah ditelaah dan diteliti. Discovery Learning merupakan model yang ditemukan oleh beberapa ahli, namun model pembelajaran ini dikembangkan oleh Jerome Bruner pada tahun 1960-an. Metode ini menekankan pada keaktifan siswa dalam belajar dan siswa dituntut untuk belajar secara mandiri dari pengalaman siswa. Namun, pembelajaran ini tidak selalu berjalan dengan efektif, karena harus menyesuaikan kemampuan siswa dan melihat situasi. Terdapat kelebihan dan kekurangan dalam Discovery Learning, namun kelemahan tersebut dapat diatasi dengan strategi tertentu.